2011
DOI: 10.1097/sla.0b013e31820784df
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy in Patients with Limited Peritoneal Surface Malignancies

Abstract: This initial investigative stage demonstrates the feasibility and safety of cytoreductive surgery and HIPEC via the laparoscopic route in selected patients with low-tumor volume and no small bowel involvement mainly from appendiceal malignancies. Longer follow-up and additional studies are required to evaluate its long-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…Similar to our effort to improve HIPEC, many surgeons have tried to improve CRS, which has low morbidity and high survival rates [18]. Shin et al reported feasibility of complete mesocolic excision with D3 lymph node dissection in laparoscopic colectomy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our effort to improve HIPEC, many surgeons have tried to improve CRS, which has low morbidity and high survival rates [18]. Shin et al reported feasibility of complete mesocolic excision with D3 lymph node dissection in laparoscopic colectomy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some centres have also performed curative intent laparoscopic CRS/HIPEC in selected patients with limited PC. Esquivel et al concluded that the laparoscopic procedure was feasible and safe in patients with an appendiceal malignancy, a low tumour volume and no small bowel involvement [56]. A longer follow-up period would be beneficial to evaluate its long-term efficacy.…”
Section: Perfusion Techniquesmentioning
confidence: 99%
“…Peritoneal cancer index (PCI) can help to select patients who will benefit from laparoscopic-CRS and HIPEC. A PCI <10 in CT scan before surgery or during laparoscopic surgery may indicate that laparoscopic CRS and HIPEC surgery may be feasible and safe by this approach [14][15][16]. In case of local peritoneal metastases recurrence, minimally invasive surgery þ HIPEC laparoscopy has shown to be a safe procedure in ovarian cancer (less surgical time, less blood losses and shorter hospital stay than open surgery).…”
Section: Discussionmentioning
confidence: 99%